Prevalence, Pattern and Sociodemographic Determinants of Near Miss Obstetrics Cases and Maternal Death at B.P. Koirala Institute of Health Sciences-A tertiary care center in Eastern Nepal - Khadka, Madan; Uprety, Dhruba Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Near misses are a woman who nearly died but survived a complication that occurred during pregnancy, childbirth, or within 42 days of termination pregnancy.Objectives: This study aims to determine the prevalence, patterns and determinants of maternal near miss and maternal death.Methodology:  This prospective Observational Study was done from August 1, 2014, to July 30, 2015, in Department of Obstetrics and Gynecology of B.P.Koirala Institute of Health sciences, Dharan. Cases eligible by five factor scoring system and WHO( World Health Organization)  near miss criteria were evaluated. Socioeconomic determinants,  prevalence and pattern of near miss and maternal death  were assessed.Result: A total of 9,727 delivery were attended during the study period. There were 6307 (71.5%) vaginal delivery and 2777(28.5%) caesarean section and 181 perinatal death with total of 9,546 live birth. Total of 162 near miss were identified and 16 maternal death occurred during the study. Maternal near miss rate of 16.6 per 1000 live birth and maternal mortality rate of 167 per 100000 live birth. Mean age of near miss and maternal death was 25.66 and 25.62 years respectively.  Obstetric hemorrhage(45%) was the leading cause of near miss and sepsis was the leading cause of death. There were 71.6% of patient admitted  to ICU, 48% were uneducated, 55.5% of near miss occurred in first pregnancy, 92.6% were unbooked patient and 37% of near miss event occurred during post-partum  period.Conclusion: Near miss and maternal death evaluation is an effective tool for  delivery of proper  health care service and help the policy makers effectively implement the laws in reducing the near miss events and thus the maternal death.